The Conflict and Preference between the Legal Evidence and the Conflict in the Prophet’s Hadith : An Applied Fundamentalist Study (Islamic Sciences Journal, 2024)
ABSTRACT        The science of the principles of jurisprudence is one of the most important sciences on which legal rulings are based for the interests of people. Among the issues related to this art is the issue of conflict and preference between legal evidence and how to combine two contradictory matters through examining the conflicting texts and knowing the abrogated and abrogated, or the earlier and later, or other controls set by the scholars of this art.      The legal texts contained in the Glorious Qur’an or the Sunnah may have conflicts - and what I will discuss in our research is this conflict in the Prophet’s hadith - and then need to be given weight within the controls and conditions.           Imam Al-Shafi’i wrote a book on various hadiths in which he addressed this issue, then scholars came after him and established general rules. A process through which the perceived conflict between the texts of Sharia is removed.      I collected this research and explained the meaning of conflict and preference, and explained the conditions for preference with applied examples that illustrate how to give weight between the texts of the Prophet’s Hadith.
Keywords: Conflict, weighting, evidence, hadiths, legitimacy, fundamentalism, applied.